The Evaluation of Skeletal Manifestations in Patients with Gaucher Disease - Çiğdem Seher Kasapkara; Asburçe Olgaç; İlyas Okur; Fatih Süheyl Ezgu; Leyla Tümer (Galenos Yayinevi, 2021)
Aim:Gaucher disease (GD) is the most prevalent hereditary lysosomal storage disorder, affecting multiple organ systems. It is characterized by a deficiency of the enzyme glucocerebrosidase leading to an accumulation of glucosylceramide in lysosomes. The majority of patients present with hepatosplenomegaly, anemia, thrombocytopenia, bleeding tendencies, skeletal pathologies, growth retardation and in severe cases pulmonary disease. The bone manifestations include bone infarcts, avascular bone necrosis, lytic lesions, osteopenia and osteoporosis. This article gives an overview of the bone manifestations of 20 GD patients and reviews the current literature.Materials and Methods:The data of 20 patients with GD who were being followed up in Gazi University Hospital Pediatric Metabolism Unit were retrospectively evaluated. Their demographic information including age, gender, clinical findings, enzyme replacement therapy (ERT) status and duration were recorded. Laboratory analyses including serum calcium, phosphorus, vitamin D, the presence of skeletal findings, and bone mineral density (BMD) Z scores were collected from the patient files. The BMD status of patients was compared with their pre-treatment values.Results:The main symptoms of referral were abdominal distention, cytopenia, bleeding tendency and skeletal findings. All patients had skeletal symptoms. Nineteen patients showed vitamin D deficiency. The medullary involvement of femur and vertebrae was present in 14 (70%), Erlenmeyer flask deformity in 3 (15%), and avascular necrosis in one (5%) patient. Also, one patient (5%) had lytic bone lesions. Ten patients showed osteoporosis (50%), and 8 showed osteopenia (40%) at the time of diagnosis, before the initiation of ERT. The rate of osteoporosis was determined to be 40%, and osteopenia was 35% within the study group after the initiation of ERT.Conclusion:Physicians, including pediatricians, may be unfamiliar with bone pathophysiology and the complexity of the skeletal manifestations of GD. There is a need to enhance awareness and to improve the diagnosis and treatment of skeletal pathology in patients with GD.